Executive overconfidence and compensation structure - Humphery-Jenner, Mark; Lisic, Ling Lei; Nanda, Vikram; Silveri, Sabatino Dino (Journal of Financial Economics, 2016)
We examine the impact of overconfidence on compensation structure. Our findings support the exploitation hypothesis: firms offer incentive-heavy compensation contracts to overconfident Chief Executive Officers (CEOs) to exploit their positively biased views of firm prospects. Overconfident CEOs receive more option-intensive compensation and this relation increases with CEO bargaining power. Exogenous shocks (Sarbanes-Oxley Act of 2002 (SOX) and Financial Accounting Standard (FAS) 123R) provide additional support for the findings. Overconfident non-CEO executives also receive more incentive-based pay, independent of CEO overconfidence, buttressing the notion that firms tailor compensation contracts to individual behavioral traits such as overconfidence.